Foreign Exchange Intervention and the Australian Dollar : Has it Mattered? - Liang, Hong (IMF Working Papers; Working Paper ;, 2003)
Since the Australian dollar was floated in December 1983, the Australian central bank (Reserve Bank of Australia) has actively intervened in the foreign exchange market. Using daily exchange rate and official intervention data from January 1984 to December 2001, this paper examines what effects, if any, foreign exchange operations by the Reserve Bank of Australia (RBA) have had on the level and volatility of the Australian dollar exchange rate. First, using an event study we evaluate the effectiveness of intervention by examining its direct effect on the level of the exchange rate. We find that over the period 1997-2001, the RBA has had some success in its intervention operations, by moderating the depreciating tendency of the Australian dollar. Second, we investigate the effects of RBA intervention policies on exchange rate volatility over the floating rate period. Our results indicate that intervention operations tend to be associated with an increase in exchange rate volatility, which suggests that official intervention may have added to market uncertainty. Overall, the effects of RBA intervention are quite modest on both the level and the volatility of the Australian dollar exchange rate.